High Level of Endotoxemia Following Out-of-Hospital Cardiac Arrest Is Associated With Severity and Duration of Postcardiac Arrest Shock*. Issue 12 (December 2015) - Grimaldi, David; Sauneuf, Bertrand; Guivarch, Elise; Ricome, Sylvie; Geri, Guillaume; Charpentier, Julien; Zuber, Benjamin; Dumas, Florence; Spaulding, Christian; Mira, Jean-Paul; Cariou, Alain
Abstract : Objective: To investigate the contribution of endotoxemia to the severity of postcardiac arrest shock. Design: A prospective monocentric study. Setting: A tertiary hospital in Paris, France. Patients: Patients admitted in our ICU after a successfully resuscitated out-of-hospital cardiac arrest. Interventions: None. Measurements and Main Results: Endotoxin measurement was performed in the 12 hours following return of spontaneous circulation using the endotoxin activity assay. Endotoxin level was classified as low (< 0.4 endotoxin activity), intermediate (0.4 to < 0.6 endotoxin activity), or high (≥ 0.6 endotoxin activity) according to manufacture guidelines. Severity of shock was assessed by the vasopressor-free days and by the mean daily dose of vasopressor to insure a mean arterial pressure of 65–75 mm Hg. Among 92 patients included in the study, 60 presented a postcardiac arrest shock. Endotoxemia level was higher in patients with postcardiac arrest shock. Among these patients, by multivariate linear regression, high endotoxin class (adjusted estimate –2.0; 95% CI, –3.90 to –0.11), public place of cardiac arrest (adjusted estimate, 1.47; 95% CI, 0.007 to 2.93), and time to return of spontaneous circulation (adjusted estimate –0.08; 95% CI, –0.13 to –0.03) were independently associated with the number of vasopressor-free days. Furthermore, high endotoxin class (adjusted estimate, 97.95; 95% CI, 20.5 to 175.4) and a nonshockable rhythm (adjusted estimate, 59.9; 95% CI, 6.2 to 113.7) were the sole factors independently associated with the mean daily dose of vasopressors. Conclusions: In patients successfully resuscitated from cardiac arrest with a postcardiac arrest shock, high level of endotoxemia is independently associated with duration of postcardiac arrest shock and the amount of vasopressive drugs. Whether treatment targeting endotoxemia could be beneficial in the management of postcardiac arrest shock needs to be studied in further randomized controlled studies. Abstract : Supplemental Digital Content is available in the text.